Association of depression and healthy behaviors in early adult mexicans - Andrade-García, Claudia L; Gutiérrez-García, Raúl A (Gaceta Médica de Caracas, 2022)
Introduction: Depressive disorders are the major cause of mental care worldwide, understanding their origin is of utmost importance to establish better diagnostic and intervention strategies, for positive short- and long-term outcomes. Aim: To establish the relationship between healthy behaviors and the level of depression in early adults by applying two assessment instruments: the Beck Depression Scale and the Fantastic Test to determine if there is a correlation between the two.